Electronic structures of layered Ta2NiS5 single crystals revealed by high-resolution angle-resolved photoemission spectroscopy. Issue 15 (21st March 2018) - Mu, Kejun; Chen, Haiping; Li, Yuliang; Zhang, Yingying; Wang, Pengdong; Zhang, Bo; Liu, Yi; Zhang, GuoBin; Song, Li; Sun, Zhe
Abstract : Using high-resolution angle-resolved photoemission spectroscopy (ARPES), we systematically studied the electronic structures of quasi-one-dimensional (1D) ternary material Ta2 NiS5 single crystals. Abstract : Using high-resolution angle-resolved photoemission spectroscopy (ARPES), we systematically studied the electronic structures of quasi-one-dimensional (1D) ternary material Ta2 NiS5 single crystals. Contrary to its sister compound Ta2 NiSe5, which is a candidate material for excitonic insulators, we found that Ta2 NiS5 cannot realize the ground state of an excitonic insulator according to temperature-dependent valence band dispersions along the Γ – X direction. In particular, the experimental ARPES data reveal that the electronic structures show strong two-dimensional characteristics along with a considerable in-plane anisotropy indicating evident coupling among the one-dimensional chain structures. Moreover, theoretical band calculations have to be compressed by a factor of about 15% in energy in order to match the experimental band structures, implying that some weak electron correlations are neglected in the band calculations.